Association of Sleep Duration and Screen Time With Anxiety of Pregnant Women During the COVID-19 Pandemic - Zhang, Yuan; Zhang, Yuge; Deng, Renli; Chen, Min; Cao, Rong; Chen, Shijiu; Chen, Kuntao; Jin, Zhiheng; Bai, Xue; Tian, Jingyan; Zhou, Baofeng; Tian, Kunming (Frontiers in Psychology, 2021)
COVID-19 pandemic has dramatically changed the pattern of lifestyle and posed psychological stress on pregnant women. However, the association of sleep duration and screen time with anxiety among pregnant women under COVID-19 pandemic scenario has been poorly addressed. We conducted one large-scale, multicenter cross-sectional study which recruited 1794 pregnant women across middle and west China. Self-reported demographic characteristics, lifestyle, and mental health status were collected from 6th, February to 8th, May 2020. We investigated the association of sleep duration and screen time with the risk of anxiety by multivariable logistic regression analysis and linear regression analysis after adjusting potential confounders. The dose-response relation of sleep duration and screen time with anxiety was visualized using cubic spline plot. Our data revealed that almost 35% of pregnant women suffered from anxiety during the COVID-19 pandemic. Sleep duration was dose-dependently associated with a lower risk of anxiety among pregnant women (OR=0.41, 95%CI: 0.27-0.63), while screen time exhibited conversed effect (OR=2.01, 95%CI:1.00-4.39). Notably, sleep duration(≥8h/day) synergistically combined with screen time(3-7h/day) to diminished the risk of anxiety (OR=0.70, 95%CI: 0.50-0.99). Taken together, sleep duration and screen time were independently and jointly associated with anxiety (P<0.05). Therefore, promoting a more active lifestyle and maintaining higher sleep quality could improve mental health of pregnant women, especially under public health emergency.